The Efforts to Settle Non-performing Loans through the Execution of Mortgage Guarantees without a Court Decision - Arif Sujatmaka; Widhi Handoko (Sultan Agung Notary Law Review, 2022)
The purpose of this study is to find out and analyze efforts to resolve non-performing loans through the execution of mortgage guarantees without a court decision and to find out and analyze the legal consequences of the execution of mortgage guarantees without going through a court decision. The research approach method used in this journal is a sociological juridical approach. . Collecting data using interview methods, document studies or library materials. After the researcher collected data, then the data obtained from the interviews and document studies were analyzed qualitatively. Qualitative data analysis, is a research method that produces descriptive data analysis, namely what was stated by the respondent in writing or verbally and also his real behavior, researched and studied as a whole. After the data analysis is complete, the results will be presented descriptively, namely by telling and describing what is in accordance with the problems studied. Furthermore, a conclusion is drawn which is the answer to the problems raised in this study. Efforts made by the Bank include collecting in the form of money to customers, restructuring credit, conducting mortgage auctions, direct write off method which is carried out when a receivable is believed to be uncollectible or repaid by the debtor, resulting in losses on receivables, directly debited to the accounts receivable loss account so that the reserve for receivables loss account is no longer used and as a result of the law the auction is null and void.